Accounting Practices and Value Relevance of Investment Property: Evidence from Firms Listed on the Stock Exchange of Thailand - Acaranupong, Kittima (Asian Journal of Business and Accounting, 2017)
Manuscript type: Research paper. Research aims: The objectives of this research are to study the accounting practices of investment property (IP) for the subsequent measurement, to investigate and compare the value relevance of the IP under the fair value model and cost model and to examine the factors affecting the accounting choices of the IP of firms listed on the Stock Exchange of Thailand. Design/ Methodology/ Approach: The regression models used in this research are based on the works of Ohlson (1995) and Feltham and Ohlson (1995) which linked the accounting information of firms with stock prices. The models are applied to test and compare the value relevance of the IP under the fair value model and cost model for the years 2011-2012. Research findings: The findings indicate that the number of Thai listed firms choosing the cost model for the subsequent measurement of the IP is considerably higher than those choosing the fair value model. The results also show that the IP is value relevant information in 2012 and in the two years’ analysis combined (2011-2012) but not in 2011. This paper reveals that the cost model of the IP is more significantly value relevant than the fair value model and that the accounting choices of the IP are significantly affected by profitability and size. Theoretical contribution/ Originality: This paper suggests that the accounting information of the IP is useful for valuing securities in the Thai stock market. The outcome also supports the bonus plan hypothesis under the Positive Accounting Theory (PAT) where higher earnings firms would predominantly use the cost model for the IP. It is further noted that larger firms in Thailand are more likely to use the fair value model for the IP, thereby supporting the size hypothesis. Practitioner/ Policy implication: The outcome drawn from this paper provides information to the Federation of Accounting Professions (FAP) in Thailand when deliberating on the revision of the accounting standards related to fair value measurements. The FAP may consider taking steps to increase the reliability of fair value so as to encourage firms to select the fair value model for use. The results can also act as a catalyst for the Securities and Exchange Commission (SEC) such that when issuing the regulation on fair value disclosures, transparency and the reliability of financial statements are further increased. Research limitation/ Implication: This paper examines the value relevance of only recognised IPs in the Statements of Financial Position. Future studies therefore, may need to investigate the relative value relevance of fair value disclosures in the notes to financial statements compared with the recognised fair value amounts of investment properties. Keywords: Accounting Practices, Investment Property, Value Relevance JEL Classification: M41, G14